Peran Taman Baca Alfabet dalam Meningkatkan Budaya Literasi Anak Dusun Kopen - Risa Istiqomah; Riske Putri Dian Syahrani; Nur Nisa’ul Insyiroh; Ayu Sri Hartini; Aisah Nur Chotimah (Academica: Journal of Multidisciplinary Studies, 2024)
Current technological developments have had several positive impacts on human survival, one of the positive impacts being the ease of accessing technology via the internet. However, besides that, there are also negative impacts such as a lack of interest in reading in children, especially young children, because children are introduced to gadgets from an early age. It is hoped that the presence of reading parks in the community can be used to increase interest in reading in young children. Kopen Sae Village Rt. 1/Rw. 7, Ngadirejo, Kartasura District, Sukoharjo Regency has a reading park called Taman Baca Alfabet Kopen Sae. The establishment of this reading park also started from the founder's empathy because young children in this modern era have lost their interest in reading. The aim of this research is to determine the role of the Kopen Sae Alphabet Reading Park in increasing children's interest in reading. The research method we use is a qualitative approach with data collection techniques using observation and interviews. The results of our research show that the Kopen Sae Alfabet Reading Park acts as a place for reading, playing, learning, dancing and storytelling. So it can be concluded that the Kopen Sae Alphabet Reading Park has a very big role in children's reading interest because there are many reading books with various reading themes.